Role of thoracic ultrasonography in pleurodesis pathways for malignant pleural effusions (SIMPLE): an open-label, randomised controlled trial - Psadillas, I; Hassan, M; Yousuf, A; Duncan, T; Leyakathali Khan, S; Blyth, KG; Evison, M; Corcoran, JP; Barnes, S; Reddy, R; Bonta, PI; Bhatnagar, R; et al. (Elsevier, 2021)
Background Pleurodesis is done as an in-patient procedure to control symptomatic recurrent malignant pleural effusion (MPE) and has a success rate of 75–80%. Thoracic ultrasonography has been shown in a small study to predict pleurodesis success early by demonstrating cessation of lung sliding (a normal sign seen in healthy patients, lung sliding indicates normal movement of the lung inside the thorax). We aimed to investigate whether the use of thoracic ultrasonography in pleurodesis pathways could shorten hospital stay in patients with MPE undergoing pleurodesis.